AMAL FIQH DALAM SISTEM PAY LATTER - Muhammad Rizqi (CV. Adiba Aisha Amira, 2026)
The development of financial technology has introduced various digital transaction innovations, one of which is the pay later system. This system allows consumers to purchase goods or services first and pay at a later date. However, the implementation of pay later raises debates within the perspective of Islamic jurisprudence (fiqh muamalah) due to the presence of additional charges, interest, and late payment penalties that potentially contain usury (riba). This study aims to analyze the legal status of the pay later system from the perspective of Islamic law and determine whether the practice is permissible ( mubah) or categorized as usury. This research employs a qualitative method with a normative-sharia approach through library research. The data sources include the Qur'an, Hadith, classical fiqh books, DSN-MUI fatwas, scientific journals, and literature related to Islamic economics and financial technology. The results indicate that the pay later system is permissible if it uses a transparent credit sale contract without interest and penalty-based charges. However, if there are additional payments due to delayed repayment or percentage-based interest, the practice falls under prohibited usury in Islam. Therefore, the use of the pay later system must comply with sharia principles to ensure lawful and fair transactions.